Decellularized Tendon Extracellular Matrix—A Valuable Approach for Tendon Reconstruction? - Schulze-Tanzil, Gundula (MDPI, 2012)
Tendon healing is generally a time-consuming process and often leads to a functionally altered reparative tissue. Using degradable scaffolds for tendon reconstruction still remains a compromise in view of the required high mechanical strength of tendons. Regenerative approaches based on natural decellularized allo- or xenogenic tendon extracellular matrix (ECM) have recently started to attract interest. This ECM combines the advantages of its intrinsic mechanical competence with that of providing tenogenic stimuli for immigrating cells mediated, for example, by the growth factors and other mediators entrapped within the natural ECM. A major restriction for their therapeutic application is the mainly cell-associated immunogenicity of xenogenic or allogenic tissues and, in the case of allogenic tissues, also the risk of disease transmission. A survey of approaches for tendon reconstruction using cell-free tendon ECM is presented here, whereby the problems associated with the decellularization procedures, the success of various recellularization strategies, and the applicable cell types will be thoroughly discussed. Encouraging in vivo results using cell-free ECM, as, for instance, in rabbit models, have already been reported. However, in comparison to native tendon, cells remain mostly inhomogeneously distributed in the reseeded ECM and do not align. Hence, future work should focus on the optimization of tendon ECM decellularization and recolonization strategies to restore tendon functionality.